2022
DOI: 10.1371/journal.pone.0268715
|View full text |Cite
|
Sign up to set email alerts
|

Visual occlusion effects on youth football players’ performance during small-sided games

Abstract: This study aimed to explore how youth players’ physical, technical and positional performance may be affected by visual occlusion when playing under different SSG pitch sizes. Under-15 players performed two experimental scenarios: a) normal situation, without visual occlusion; b) visual occlusion, by using an eye patch in the eye corresponding to the dominant foot. These scenarios were tested in a small (40x30m) and a larger pitch (50x35m). Players’ positional data was used to compute tactical and time-motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…From the results obtained, it can be confirmed that football performance depends largely on the visual perceptual system that provides information for perception and action (Vaeyens et al, 2007). Furthermore, this study provided key information regarding how the players adjust their behaviour as a result of temporary occlusion (Santos et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…From the results obtained, it can be confirmed that football performance depends largely on the visual perceptual system that provides information for perception and action (Vaeyens et al, 2007). Furthermore, this study provided key information regarding how the players adjust their behaviour as a result of temporary occlusion (Santos et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…Small-sided games (SSG) were conducted on fields of different dimensions following the design outlined by Santos et al (2022). The study employed a specialized training format called Gk+4vs4+Gk Small-Sided Game (SSG) to investigate the effects of different experimental scenarios on player performance.…”
Section: Methodsmentioning
confidence: 99%